Antibacterial Activity of Ethyl Acetate Extract of Red Ginger (Zingiber officinale Roscoe var. Sunti) Against Bacteria of Staphylococcus aureus and Escherichia coli - Sari Purbaya; Lilis Siti Aisyah; Jasmansyah Jasmansyah; Wenny Eliza Arianti (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2018)
Red ginger rhizome (Zingiber officinale Roscoe var. Sunti) is one of the herbs that is widely used as traditional medicine. The present study was to determine the secondary metabolites contained in red ginger rhizome plants and antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria. A total of 483.2 grams of red ginger powder was extracted by maceration method obtained from ethyl acetate extract 15.85 g. Antibacterial activity of red ginger extract against S. aureus and E. coli using microdilution method showed that ethyl acetate extract could inhibit S. aureus growth by MIC (Minimum Inhibitory Concentration) 6.3% and MBC (Minimum Bactericidal Concentration) 25% and extract Ethyl acetate red ginger rhizome can Minimum MIC (E. Inhibition Concentration) E. coli with a minimum inhibitory concentration of 25% and MBC (Minimum Bactericidal Concentration) 50%. The results showed that the red ginger rhizome ethyl acetate extract was the most influential and had more potential to inhibit the growth of Gram positive bacteria compared to inhibition of Gram negative.